Walled-Off Necrosis: Safety of Watchful Waiting - Wroński, Marek (Dig Dis Sci, 2014)
BACKGROUND: Asymptomatic pancreatic necrosis should be managed conservatively, regardless of its extent. However, late sequelae and safety of non-interventional management in patients with asymptomatic walled-off necrosis remain unclear. AIMS: The purpose of this study was to report the clinical outcome of outpatient expectant management in a cohort of patients with walled-off necrosis who were discharged asymptomatic after an episode of acute pancreatitis. METHODS: Sixteen patients with walled-off necrosis asymptomatic at discharge were identified retrospectively from a single institution. Data were analyzed for the type of complications, their incidence and treatment. RESULTS: Seven of 16 patients (44 %) did not experience any complications during a median follow-up of 17 months. Nine of 16 patients (56 %) became symptomatic or developed complications within a median follow-up of 49 days after discharge. The most common complication was infection of pancreatic necrosis which occurred in 7 of 9 patients. Six of these patients were successfully treated with minimally invasive techniques. In 5 of 7 patients, infection of necrosis was due to oral commensal bacteria. Acute intracavitary hemorrhage and intractable abdominal pain developed in one patient each. There was no mortality in this series. CONCLUSIONS: Outpatient watchful waiting can be used safely in patients with asymptomatic walled-off necrosis, although nearly half of them eventually develop complications which require interventional treatment. Most late infections of pancreatic necrosis are probably due to a blood-borne transmission of oral commensal bacteria.